Isothermal crystallizatoin kinetics of methyl laurate - Lagrimas, Charine Faith H. (College of Engineering, University of the Philippines Diliman, 2014)
Avrami model parameters are used to describe the isothermal crystallization kinetics of methyl laurate from Differential Scanning Calorimetry (DSC) measurements. The amount of methyl laurate considered is 10mh for all DSC measurements using a cooling rate of -2.5°C/min (Galvan, 2014). At 3°C, parameters from step-wise Avrami model show that methyl laurate exhibits a secondary crystallization. The primary crystallization occurs with instantaneous nuclei and sperulitic growth; with an overall crystallization rate of 0.0019/m3. This is followed by a secondary instantaneous nucleation with a lower growth of dimensionality, red-like, with a faster overall crystallization rate of 0.1067/min. Normal Avrami model is used for the assumed isokinetic range, 4°C and 6°C. the kinetics behaviour is the same which is instantaneous nucleation with one-dimensional growth. The overall crystallization rates are 0.02768/min, 0.0270/min and 0.0118/min for 4°C, 5°C and 6°C respectively. The differences for the isokinetic range temperatures are the activation energies (directly proportional to T) and nucleation rates (inversely proportional to T). From the images obtained during the crystallization of methyl laurate, it is confirmed that the nucleation and crystal growth modes obtained from the optical microscope are consistent with the parameters from Avrami model.